The Integration of Democratic Values in Learning from an Islamic Education Perspective - Mumtahana, Lusia; Madkan, Madkan (STAI MA'ARIF MAGETAN, INDONESIA, 2024)
This article aims to analyze and describe democratic values in learning from the perspective of Islamic education. The study employs a qualitative method with a library research approach. The findings reveal that implementing democracy in the learning process is crucial, especially because students come from diverse backgrounds. Before teaching, educators must understand the characteristics of each student to select appropriate methods for effective instruction. Applying democratic principles in teaching, such as openness, encourages students to be more active, creative, and collaborative, thereby facilitating the achievement of educational goals. To realize democratic learning, several approaches can be implemented: an individual approach, tailored to the specific needs of each student; a group approach, emphasizing collaboration; an experiential approach, grounded in direct practice; a habitual approach, to consistently instill positive values; and an emotional approach, fostering harmonious relationships between teachers and students. By integrating democratic values into the learning process, Islamic education can become more inclusive, relevant, and adaptive to the needs of students.